The dynamics of the relationship between the Kotaagung Village government and the farmers group in the practice of Saemaul Undong values - Ahmad, Azis; Mahmud, Imam (Priviet Social Sciences Journal, 2025)
This study examines the dynamics of the relationship between the Kotaagung Village Government and farmer groups in adopting and implementing Saemaul Undong values as a community-based development strategy. Values such as independence, hard work, and solidarity serve as normative frameworks for interactions between state actors at the local level and farmer communities in efforts to improve food security and village welfare. Using a qualitative descriptive approach and data collection techniques, including in-depth interviews, participatory observation, and documentary studies, this study found that the relationship between the village government and farmer groups is dynamic and influenced by factors such as local leadership, institutional capacity, patterns of communication, and social trust. Despite challenges in terms of program consistency and the active participation of farmers and their groups, the practice of Saemaul Undong values successfully facilitates more productive collaboration in the planning and implementation of collective agricultural activities. This study recommends strengthening collaborative governance based on local transformative values as a foundation for sustainable village development in Indonesia.